2018
DOI: 10.1111/eip.12731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antenatal depression screening and intervention among Chinese high‐risk pregnant women with medically defined complications: A randomized controlled trial

Abstract: This study highlights the effectiveness of the screening and the targeted management of antenatal depression in Chinese high-risk pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
3
8
0
4
Order By: Relevance
“…We found that awareness of antenatal depression increased, not only among the intervention group, but also among the control group, due to the implementation of antenatal depression screening and follow-up, in line with our previous study (Zhao et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that awareness of antenatal depression increased, not only among the intervention group, but also among the control group, due to the implementation of antenatal depression screening and follow-up, in line with our previous study (Zhao et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…We found that awareness of antenatal depression increased, not only among the intervention group, but also among the control group, due to the implementation of antenatal depression screening and follow‐up, in line with our previous study (Zhao et al, 2019). For most women enrolled in the study, concern for their psychological health and potential negative effects on their foetus led to proactive adjustments to unstable emotions during the perinatal period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After the announcement of the human-to-human transmission, and the declaration of lockdown policy on 23rd January, 2020 in Wuhan, China, there was a significant rise in the prevalence of anxiety, and depressive symptoms amongst pregnant women ( 1 , 14 ). To reduce the adverse consequences of psychological disturbances reported within this population, experts suggested that screening should be implemented with adequate systems to ensure accurate diagnosis, effective treatment, and appropriate follow-up ( 34 ). In late February, the national health authorities and Chinese academic societies published specific expert consensus and intervention guidelines, appropriately labeled, “The Manual of Novel Coronavirus Pneumonia Prevention and Control for Children and Pregnant Women” ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to evaluate the efficacy of breastfeeding interventions (Franco-Antonio et al, 2019). Because perinatal depression is under-diagnosed in China, and many women do not receive sufficient support (Zhao et al, 2019), there is a great need to increase health care providers’ awareness of risk for perinatal depression and improve access to efficient and acceptable interventions to enhance breastfeeding and promote postpartum psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%